2018
DOI: 10.1055/s-0038-1670649
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Anatomy at the “Box Junction”: Considerations in the Anterolateral Thigh Flap

Abstract: Our study confirms that the BxJn is a site of potentially complex and challenging neurovascular anatomy for the surgeon. Based on these results, we propose an algorithm to guide inexperienced surgeons in negotiating this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Although there have been several anatomical studies on the lateral femoral circumflex artery 2 , 8 10 and motor nerve of the vastus lateralis muscle 7 , 11 , 12 on their own, the anatomical relationship between them has rarely been reported. 13 15 …”
Section: Purposementioning
confidence: 99%
See 4 more Smart Citations
“…Although there have been several anatomical studies on the lateral femoral circumflex artery 2 , 8 10 and motor nerve of the vastus lateralis muscle 7 , 11 , 12 on their own, the anatomical relationship between them has rarely been reported. 13 15 …”
Section: Purposementioning
confidence: 99%
“… 14 Stewart et al reported the neurovascular anatomy at the “box junction,” the point at which the perforator arose from the source vessel. 15 However, the overall anatomy of these two were not assessed in previous studies, and their detailed anatomical relationship is still unclear. This study aimed to investigate the overall anatomic locations of the perforators from the descending branch of the lateral femoral circumflex artery and the motor nerve branches of the vastus lateralis muscle using fresh-frozen cadaveric specimens and to determine which branches of the motor nerve are at a higher risk of injury.…”
Section: Purposementioning
confidence: 99%
See 3 more Smart Citations